DDX3Y gene rescue of a Y chromosome AZFa deletion restores germ cell formation and transcriptional programs - Ramathal, Cyril (Sci Rep, 2015)
Deletions of the AZFa region (AZoospermia Factor-a) region of the human Y chromosome cause irreversible spermatogenic failure that presents clinically in men as Sertoli-cell only (SCO) pathology of the testis. Deletions of the AZFa region typically encompass two genes: DDX3Y and USP9Y. However, human genetic evidence indicates that SCO is most tightly linked to deletion of DDX3Y and that deletions/mutations of USP9Y can be transmitted from one generation to the next. Here, we generated stable iPSC lines with AZFa deletions, tested complementation via introduction of DDX3Y, and assessed ability to form germ cells in vivo in a xenotransplantation model. We observed a quantifiable improvement in formation of germ cell like cells (GCLCs) from complemented donor iPSCs. Moreover, expression of UTF1, a prospermatogonial protein, was restored in cells complemented by introduction of DDX3Y on the AZFa background. Whole-genome RNA sequencing of purified GCLCs revealed an enrichment of genes involved in translational suppression and transcriptional control in DDX3Y-rescued GCLCs over mutant GCLCs, which maintained a molecular phenotype more similar to undifferentiated iPSCs. This study demonstrates the ability to probe fundamental genetics of human germ cell formation by complementation and indicates that DDX3Y functions in the earliest stages of human germ cell development.